Hubungan Efikasi Diri Pengasuhan terhadap Kecemasan Orangtua Anak dengan Autisme - Yasmin Meutia Solihati (Fakultas Psikologi, Universitas Putra Indonesia YPTK Padang, 2021)
This research aims to determine the relationship between parenting self efficacy, and anxiety of parents with autism children. This study involved 41 parents aged 27 to 60 years old and had children autism with 5 to 12 years old. Anxiety scale, gratitude scale, parenting self efficacy scale, and social support scale was used to collect the data. This Research using the product moment method with IBM SPSS Statistic Version 22 to analyze the data. The results showed that there was a relationship between parenting self-efficacy on the anxiety of parents of children with autism with a value of r = 0.257 and p = 0.000.